Information Organization and Information Interaction in Social tagging Sites: A Comparative Examination of Interface Features and Functionalities - Shiri, Ali; Storie, Dale (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The aim of this paper is to report on an investigation of information organization and information interaction issues in social tagging sites based on interface features and functionalities. The paper will provide a comparative examination of tag related features and functionalities in ten popular social tagging sites. L’objectif de cet article consiste à présenter une étude sur les questions de l’organisation et l’interaction de l’information dans les sites d’étiquetage social, et plus particulièrement de présenter les caractéristiques et fonctionnalités de l’interface. Cet article offre une analyse comparative des étiquettes liées aux caractéristiques et fonctionnalité de dix sites d’étiquetage social des plus populaires.